079 Glial fibrillary acidic protein (GFAP) astrocytopathy associated with cerebral micro-infarction and poor therapeutic response. (29th July 2019) - MacDonald, Allycia; Triplett, James; Vijayan, Srimathy; Bynevelt, Michael; Lakshmanan, Rahul; Chemmanam, Thomas
Abstract : Introduction: Glial fibrillary acidic protein (GFAP) astrocytopathy is a lesser recognised immune-mediated meningo-encephalomyelitis, which is steroid responsive in the majority of cases. Neuroimaging is unique with a distinctive symmetric white matter perivascular linear and punctate enhancement pattern. We present a case with classical phenotype but delayed clinical response, and highlight the importance of early recognition and treatment. Case: A 59-year-old Caucasian female presented with a two month history of headache, gait disturbance, insomnia, agitation, disorientation and reduced oral intake. Examination revealed a high frequency upper limb tremor, hypertonicity and pathologically brisk reflexes with impaired cognitive function. MRI brain and spinal cord demonstrated high T2 signal and striking perivascular and punctate enhancement in supratentorial white matter, cervical and upper thoracic cord. CSF examination revealed lymphocytic pleocytosis and elevated protein. Brain biopsy demonstrated reduced GFAP expression, perivascular T-lymphocytic infiltrate, and recent white matter microinfarction. CSF and serum GFAP antibodies were positive. Motor deterioration accompanied progression to a stuporous state. High dose corticosteroids were commenced, followed by intravenous immunoglobulin and mycophenolate. While there was marked improvement of perivascular contrast enhancement on imaging, the patient continued to demonstrate prominent tremor, gait disturbance and behavioural issues 9 months following symptom onset. Conclusions: The persistence of disability in this case is likely the result of axonal loss from the initial insult, reflected by the biopsy evidence of microinfarction. Awareness of the unique pattern on MRI and the clinical phenotype will aid in early recognition and prompt treatment of this condition, thus preventing the potential long term morbidity.